PENERAPAN METODE EVERYONE IS TEACHER HERE UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SD NEGERI CEMPAKA BARU 07 PAGI JAKARTA - Dwi Rahmah Inayati; Ati Kusmawati (Khazanah Pendidikan, 2020)
ABSTRACTThis research is motivated by the existence of student learning outcomes in social sciencesubjects Theme 8 Sub theme 3 Material Types of Business and Economic Activities underthe KKM, so that the writer is moved to research and propose solutions by applying theEveryone is Teacher Here method. The purpose of this study was to improve socialstudies learning outcomes in fifth grade students at SDN Cempaka Baru 07 Pagi. Themethod used is classroom action research. The study was conducted in two cycles withindicators of the success of students' scores in the cognitive domain ≥ 70, in the affectivedomain ≥ 2.33 with the B-category, in the domain of skills category B, mastery learning≥ 70% and learning outcomes in cycle II> of cycle I. The results showed the averagevalue of students from 47.42 in the pre cycle increased to 49.36 at meeting 1, increasedto 56.77 at meeting 2. At cycle II meeting 1 increased again to 68.55 and meeting 2 to74,19. The percentage of pre-cycle study completion 19.35% increase in cycle I meeting1 to 25.81%, meeting 2 to 51.61%, cycle II meeting 1 to 77.42% and meeting 2 to80.65%. The average value of affective learning outcomes in cycle I was 3.27 (B +), thenincreased in cycle II to 3.52 (A). The learning outcomes of the first cycle skill get anaverage score in category C and increase in cycle II to category B. This shows that theeveryone is Teacher Here method can improve the learning outcomes of social studiesin class V students of SDN Cempaka Baru 07 Pagi.Keywords: Everyone is Teacher Here Method, Learning Outcomes, and Social StudiesSubjects.